Writing the History of the Roman Lusitania today: methods, concepts and documents - Bina, Tatiana (Romanitas - Revista de Estudos Grecolatinos, 2014)
Review of: LE ROUX, P. Os territórios romanos de Portugal no Alto Império. Revista do Museu de Arqueologia e Etnologia da USP, suplemento 19, 2015.
Keywords: Roman Empire; Iberian Peninsula; Lusitania; Territory